The Idea of ‘Landscape Cultivation’ by Adam Wodziczko - Gawor, Leszek (Problemy Ekorozwoju, 2019)
The article presents the concept of landscape cultivation of Adam Wodziczko, a Polish naturalist and propagator of environmental protection in Poland in the 1920s and 1940s. It demonstrates the importance of his idea of the contemporary trend of landscape ecology; his merits in the field of building the basics of the science of nature conservation; and the role he played in nature conservation in Poland.